FEATURES OF TEACHING LEXICAL SKILLS IN THE CLASSROOM - Usarova Nilufar Yakubovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses about the readiness of children to learn and the change of leading activity - from playing to learning activities. Additionally, lexical skills were explained with the help of different methods in order to attract learner’s attention in the classroom and in the process of learning, scientific concepts are formed in younger students.